2022
DOI: 10.1109/ted.2022.3177388
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electron Effective Mass in AlGaN/GaN Heterostructures by THz Spectroscopy of Drude Conductivity

Abstract: Terahertz time domain spectroscopy (TDS) of the two-dimensional (2-D) electrons in various commercial AlGaN/GaN heterostructures was performed in the frequency range of 0.1-2.0 THz at selected temperatures of 80 and 300 K. Experimental transmission spectra were analyzed using analytical model derived for the thin conductive layer on dielectric substrate assuming a highfrequency Drude response of electrons. Two-dimensional electron mobility and density values found from the best fit parameters were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In general, the response of the hot carrier detector begins to decrease as the detected frequency approaches the inverse of the momentum relaxation time τ p [8]. The measured Drude conductivity of 2DEG in the AlGaN/GaN structures at room temperature revealed that the carrier relaxation time at low electric field was about 0.3 ps [25]. This suggests that the theoretical cut off frequency for BT diodes could be about 1 THz.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In general, the response of the hot carrier detector begins to decrease as the detected frequency approaches the inverse of the momentum relaxation time τ p [8]. The measured Drude conductivity of 2DEG in the AlGaN/GaN structures at room temperature revealed that the carrier relaxation time at low electric field was about 0.3 ps [25]. This suggests that the theoretical cut off frequency for BT diodes could be about 1 THz.…”
Section: Resultsmentioning
confidence: 95%
“…Compared to previously used GaAs-material systems, the selected material has an advantage of a higher electron density, which is useful for a better match between the THz sensor and asymmetric BT antenna impedances [7]. In addition, the short momentum relaxation time of electrons ensures the THz coupling to the 2DEG layer [25,26]. Furthermore, good ohmic contacts to 2DEG in AlGaN/GaN heterostructures can be obtained without the heavy doping of semiconductor layers.…”
Section: Introductionmentioning
confidence: 99%
“…For silicon based heterointerface devices however, it is important to note that the lowest energies of the conduction band are not symmetrical, as the constant-energy surfaces are now ellipsoids, rather than the spheres in the case of the III-V materials discussed in (1). Each conduction band minimum can be approximated only by…”
Section: Composite Channel Selectionmentioning
confidence: 99%
“…Composite channel HEMTs attempt to master the governance of electron flow and channel formation within the device by maximizing planar electron concentration at the heterointerfaces and confining the electrons accumulated with the help of a potential energy barrier on either side of the channel. A charge carrier, upon moving from one band to another experiences a change in effective mass dependent on the energies of the bands involved [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…One of such methods is the THz-TDS system, which has been adapted for such applications [83][84][85][86]. The THz transmission spectra were analyzed considering graphene on the dielectric substrate as the delta-thin conductive layer, which is described by the Drude conductivity model, with fitting parameters of sheet conductivity S σ , scattering time S C τ , and substrate thickness S d [84,85,87]. The transmission spectrum of the graphene sample is shown in Figure 8 by red circles and a fitted curve (black line), which coincide well with experimental points.…”
Section: Electrical Properties Of Graphene After Pmma Removalmentioning
confidence: 99%